Electromagnetic interactions and hadronic structure - Close, F. E.; Donnachie, Sandy 1936-; Shaw, G. 1942- (Cambridge University Press, 2007)
The distribution of quarks within protons and neutrons, their interactions, and how they define the properties of protons, neutrons and nuclei, are subjects of major research worldwide. Written by leading experts in the field, both theoretical and experimental, this book provides an authoritative overview on the subject. The emphasis throughout the book is on phenomenology, and the book concentrates on describing the main features of the experimental data and the theoretical ideas used in their interpretation. Sections on chiral perturbation theory, crucial in understanding soft pions and soft photons near threshold, and duality ideas, equally crucial at intermediate energies, are included. This is an essential reference for graduate students and researchers in the field of particle physics and electromagnetic interactions.